Modelling analysis of PAH and soot measured in a premixed toluene-doped methane flame. (15th December 2018) - Russo, C.; Ciajolo, A.; D'Anna, A.; Sirignano, M.
Abstract: A detailed gas-phase kinetic model coupled with a multi-sectional approach for the particle phase was used for inferring the effect of toluene addition on the sooting structure of a fuel-rich laminar premixed methane flame. Premixed methane flames at different C/O ratios established the reference environments to gain insight on the influence of toluene addition. Experimental data derived from a detailed analysis of the combustion aerosol sampled along the methane flame and the toluene-doped flame, burning in similar temperature conditions, were compared with the predictions of the model to assess its sensitivity to small changes in the fed mixture composition. Modeling results predicted reasonably well the gas- and the particle-phase concentrations. Overall, the effect of small amounts of toluene on the sooting yield and structure of the methane flame strongly tending toward the sooting structure typical of aromatic fuels, was observed. Experimental evidences and modeling results suggest that the relative importance of soot inception and surface growth by C2 H2 and PAH onto existing particles or aggregates is significantly affected by toluene addition.